Androgen status in non-diabetic elderly men with heart failure. (2nd October 2017) - Loncar, Goran; Bozic, Biljana; Neskovic, Aleksandar N.; Cvetinovic, Natasa; Lainscak, Mitja; Prodanovic, Nenad; Dungen, Hans-Dirk; von Haehling, Stephan; Radojicic, Zoran; Trippel, Tobias; Putnikovic, Biljana; Markovic-Nikolic, Natasa; et al.
Abstract: Purpose: We aimed at evaluating androgen status (serum testosterone [TT] and estimated free testosterone [eFT]) and its determinants in non-diabetic elderly men with heart failure (HF). Additionally, we investigated its associations with body composition and long-term survival. Methods: Seventy three non-diabetic men with HF and 20 healthy men aged over 55  years were studied. Echocardiography, 6-min walk test, grip strength, body composition measurement by DEXA method were performed. TT, sex hormone binding globulin, NT-proBNP, and adipokines (adiponectin and leptin) were measured. All-cause mortality was evaluated at six years of follow-up. Results: Androgen status (TT, eFT) was similar in elderly men with HF compared to healthy controls (4.79  ±  1.65 vs. 4.45  ±  1.68  ng/ml and 0.409  ±  0.277 vs. 0.350  ±  0.204  nmol/l, respectively). In HF patients, TT was positively associated with NT-proBNP ( r =  0.371, p  =  0.001) and adiponectin levels ( r   =  0.349, p  =  0.002), while inverse association was noted with fat mass ( r  =  −0.413, p  <  0.001). TT and eFT were independently determined by age, total fat mass and adiponectin levels in elderly men with HF ( p   <  0.05 for all). Androgen status was not predictor for all-cause mortality at six years of follow-up. Conclusions: In non-diabetic men with HF, androgen status is not altered and is not predictive of long-term outcome.